THE CHANGING SENSE OF POLITENESS IN FEMALE CHARACTERS IN MARGARET MITCHELL'S GONE WITH THE WIND - Rendra Bening Prakoso (Soegijapranata Catholic University, 2009)
Sense of politeness in language is an important aspect in human interaction. Since it is dealing with society,this makes politeness something flexible based on place and time. It means that what is meant by word